Social Media Impersonation in the Virtual World - Mohammed A Gharawi; Ahmed Badawy; Doaa Elsayed Ramadan; Shaymaa Elsayed (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
Introduction: Social media is becoming a critical part of everyone’s life. Social media has numerous platforms including Facebook, Twitter, Instagram, and LinkedIn. Impersonation is a common phenomenon found nearly on all social media platforms; it is the act of attempting to deceive someone by pretending that he is another person. Impersonators always try to hide a real account by making another similar profile to spread the fake contents on social media platforms making it very difficult to know the real accounts from the fake ones. Aims: This paper aims to write a comprehensive review on the social media impersonation, impersonation types, how to identify the social media impersonation, cases of social media impersonation, how to prevent impersonation, and how to protect the security of a social media user. Besides, the article explains the position of Islam toward impersonations including social media impersonation. Method: This is a narrative review of the existed literature review on the social media impersonation in the virtual world. Conclusion: Social media impersonation is the act of pretending that a person is another person which usually occurs on all social media platforms.